ANALISIS PEMETAAN (SOCIAL MAPPING) PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI INDONESIA - Riza, Faizal; Afrizal, Ardi (Journal of Business Studies and Management Review, 2026)
This study, entitled Social Mapping Analysis of Corporate Social Responsibility (CSR) Programs in Indonesia, employs a descriptive analytical method to examine the paradigm shift in the implementation of Corporate Social Responsibility (CSR) in Indonesia from conventional philanthropy toward strategic social investment. The predominance of the education (30–40%) and economic empowerment (20–25%) pillars reflects growing corporate awareness of the need to address gaps in community competencies and financial self-reliance. Education is positioned as an instrument for the long-term improvement of human resource quality, while the empowerment of micro, small, and medium enterprises (MSMEs) serves as an exit strategy to prevent economic disruption in communities once company operations cease. Program effectiveness depends substantially on community perceptions and the approach adopted in implementation. Participatory programs involving community leaders (local heroes) through social mapping tend to achieve higher levels of acceptance because they are more relevant to local needs and maintain greater transparency. As a strategic recommendation, companies need to shift their perspective from viewing CSR as a cost center to treating it as a form of social investment by identifying local actors who possess integrity and influence. The active involvement of community leaders can ensure that CSR programs move beyond ceremonial activities and generate tangible improvements in community well-being while supporting the long-term sustainability of business operations in the areas where companies operate.